THE IMPACT OF GENDER AND SECOND LANGUAGE PROFICIENCY ON WILLINGNESS TO COMMUNICATE IN THE UPPER SECONDARY SCHOOLS OF GJILAN TOWNKOSOVO - Ymeri, Mejreme (PEOPLE: International Journal of Social Sciences, 2016)
Second language willingness to communicate (WTC) has lately become an important concept in second language learning and communication. Earlier research on willingness to communicate (WTC) has shown that there are a lot of factors that influence the willingness of the learners to communicate and among those factors there are mentioned also the factor of gender and the language proficiency. The objectives of the study were to identify the factors that influence willingness to communicate and to find out if the gender and language proficiency have any effect on willingness to communicate. In addition, by this study there is intended to provide information to teachers in order to help their students feel more confident in expressing themselves. This study included a questionnaire with upper-secondary school students. In order to measure students' willingness to communicate there was administered a modified version of the Likert-type questionnaire developed by MacIntyre et al. (2001). A total of 300 hundred upper-secondary schools students participated in the study. Results from the study do not show that the gender of the students plays a noteworthy role on their willingness to communicate respectively based on the results female students are just a little bit more willing to communicate compared to male students. On the other side the proficiency of the students has a notable effect on the willingness of the students to communicate respectively proficient students are much more willing to communicate than the non-proficient students.